The “Super-Fontan” Phenotype: Characterizing Factors Associated With High Physical Performance - Tran, Derek L.; Celermajer, David S.; Ayer, Julian; Grigg, Leeanne; Clendenning, Carley; Hornung, Tim; Justo, Robert; Davis, Glen M.; d'Udekem, Yves; Cordina, Rachael (Frontiers in Cardiovascular Medicine, 2021)
Background: People with a Fontan circulation usually have moderately impaired exercise performance, although a subset have high physical performance (“Super-Fontan”), which may represent a low-risk phenotype. Methods: People with a “Super-Fontan” phenotype were defined as achieving normal exercise performance (≥80% predicted peak oxygen uptake [VO2] and work rate) during cardiopulmonary exercise testing (CPET) and were identified from the Australian and New Zealand Fontan Registry. A Fontan control group that included people with impaired exercise performance (<80% predicted VO2 or work rate) was also identified based on a 1:3 allocation ratio. A subset of participants were prospectively recruited and completed a series of physical activity, exercise self-efficacy, and health-related quality of life questionnaires. Results: Sixty CPETs ("Super-Fontan", n=15; control, n=45) were included. A subset ("Super-Fontan", n=10; control, n=13) completed a series of questionnaires. Average age was 29±8 years; 48% were males. Exercise capacity reflected by percent predicted VO2 was 67±17% in the entire cohort. Compared to the “Super-Fontan” phenotype, age at Fontan completion was higher in controls (4.0±2.9 versus 7.2±5.3 years, p=0.002). Only one (7%) person in the “Super-Fontan” group had a dominant right ventricle compared to 15 (33%) controls (p=0.043). None of those in the “Super-Fontan” group were obese, while almost a quarter (22%) of controls were obese based on body mass index (p=0.046). Lung function abnormalities were less prevalent in the “Super-Fontan” group (20% versus 70%, p=0.006). Exercise self-efficacy was greater in the “Super-Fontan” group (34.2±3.6 versus 27.9±7.2, p=0.02). Self-reported sports participation and physical activity levels during childhood and early adulthood were higher in the “Super-Fontan” group (p<0.05). The total average time spent participating in structured sports and physical activity was 4.3±2.6 hrs/wk in the “Super-Fontan” group compared to 2.0±3.0 hrs/wk in controls, p=0.003. There were no differences in self-reported current total physical activity score or health-related quality of life between groups (p≥0.05). Conclusions: The “Super-Fontan” phenotype is associated with a healthy weight, lower age at Fontan completion, better exercise self-efficacy, and higher overall levels of sport and physical activity participation during physical development.